Influence of N-Power on the entrepreneurial spirit and business start-up rates among youth in Anambra State - Nonso Sunday Okoye; Benjamine Victor Anekwe; Achinike Daniel Chimaobim; Alexander Tochukwu Okoye (PT. BATARI EDU CALYA, 2026)
A major socio-economic issue in Nigeria is youth unemployment which has led the government to initiate the N-Power intervention programmes to complement youth empowerment and entrepreneurship development. The current research adopted a descriptive survey design to investigate the N-Power recipients in six Local Government Areas of the state of Anambra. A sample of 343 was sampled out of 2,412 youths in the age group of 18 to 35 based on the formula of Taro Yamane and proportionately distributed according to Bowleys method. The information was collected through a structured 5-point Likert questionnaire. The expert review ensured face and content validity, whereas reliability was tested by a testretest procedure. The statistical data were analyzed with SPSS and Pearson correlation coefficients were computed at a significance level of 5 5-percent. Results show that most of the respondents felt that the N-Power programme had influenced positively entrepreneurship spirit and business start ups among the young people in Anambra State. A significant percentage of them reported to have been better equipped in the programme to start businesses, to get jobs, and to be supported or counselled on starting businesses. A good number of the respondents also indicated that they would recommend the programme to other job seekers. In addition, Pearson correlation analysis (r=.199,p=.05) demonstrated a statistically significant positive correlation between N-Power participation and the business start-up rates among the youths. The research determined that N-Power programme is central in encouraging youth entrepreneurship in Anambra State and advised the government to enhance the program by offering better training, start-up capital and post-programme mentorship with the aim of fostering sustainable business activities among youth beneficiaries.